Visualization in Engineering - Wang, XiangYu; Kang, Shih Chung Jessy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Visualization in Engineering publishes original research results regarding visualization paradigms, models, technologies, and applications that contribute significantly to the advancement of engineering in all branches, including medical, biological, civil, architectural, mechanical, manufacturing, industrial, aerospace, and meteorological engineering and beyond. The journal solicits research papers with particular emphasis on essential research problems, innovative solutions, and rigorous validations. All submitted articles should explicitly include these three main elements. The journal publishes content in the form of research articles, review papers, technical notes, and case studies. These original papers typically: report the latest progress in the engineering discipline with regard to applying visualization methods are relevant to visualization and help to provide a scientific basis by which decision-making in engineering becomes more reliable, spontaneous, and creative contain novel research that demonstrates the science behind knowledge-intensive engineering tasks validate the generality, power, and scalability of new methods through rigorous evaluation, both qualitatively and quantitatively conduct rigorous reviews of state-of-the-art visualization technologies that facilitate engineering tasks demonstrate practical and robust case studies in which innovative approaches are implemented. The journal is particularly interested in research that adds to the scientific understanding of the impacts that visualization technologies can have on the stages along the entire life cycle of a particular industry, for example, planning, design, construction, maintenance, and operations of constructed facilities. Visualization in Engineering provides, for the first time, an international and interdisciplinary platform and forum for researchers to present their findings, latest developments, and perspectives on future trends in visualization in design and engineering, covering relevant advances in the areas of computing, management, human factors, education, and social sciences.
Keywords: Engineering; Computer-aided engineering; Industrial design; Engineering design; Engineering; Engineering Design; Computer-Aided Engineering (CAD, CAE) and Design; Industrial Design